Construction of a performance evaluation index system for the management of chronic diseases based on medical and preventive integration - Mingqing Zhao; Ziyi Cheng; Zhuqing Chen; Qi Wang; Junan Liu (BMC Public Health)
Abstract Background The medical and preventive integration(MPI) brings significant and substantial benefits to chronic disease management (CDM). Evaluating the effectiveness of MPI is curial to promote the high quality development of CDM. However, such a tool is not available in this field. We aimed to develop an evaluation index system for assessing the regional performance management level of MPI in the CDM and provide suggestions for improving quality construction of CDM at the county level. Methods The initial version of the performance evaluation index system was constructed based on literature analysis, panel discussions, and in-depth on-site interviews. The Delphi questionnaire was designed and 24 experts in the field of CDM were consulted in two rounds. The analytic hierarchy process method was employed to calculate the weight of indexes at the three levels. Results The MPI performance evaluation index system at the county level includes five first-level indexes, 20 s-level indexes, and 69 third-level indexes. Among the five first-level indicators, “integration quality” (0.2060) ranked first, followed by “integration inputs” (0.2010), “integration effectiveness” (0.1982), “integration outputs” (0.1975), and “integration mode” (0.1973). Conclusion The MPI performance evaluation indexes for CDM at the county level are scientific and reliable. This system can act as a useful tool for diversified subjects to find the loopholes and weak points in CDM. It also provides valuable experience for other national authorities to further improve their own CDM system by MPI evaluation. Strengths and limitations of this study This study complements the gaps in the field of MPI questionnaires in China, but the sample size is small, and it is recommended that reliability and validity tests be carried out in multiple regions of the country in later stages to increase the practicality of the questionnaire.